Mechanical and physical characteristics of knee flexors and extensors following different warm up protocols in collegiate male soccer athletes - Redd, M. J. (University of Central Florida, 2018)
PURPOSE: To compare potential differences in mechanical and physical characteristics of knee flexors and extensors in collegiate male soccer players following different warm up protocols. METHODS: Sixteen collegiate male soccer players (20.33 ± 1.33 years, 176.97 ± 6.72 cm, and 78.43 ± 7.42 kg) participated in this study. A small sided games warm up (SSG), a dynamic warm up (DYN), and a plyometric warm up (PLY) were completed using a randomized crossover design. Tensiomyography (TMG) was used to assess contraction time (Tc), delay time (Td) and maximal displacement (Dm) of the rectus femoris (RF) and biceps femoris (BF) of both legs before (PRE) and after (POST) each warm up. POST assessment included: TMG of the RF and BF, countermovement jump height (CMJ-h), CMJ flight time (CMJ-ft), 20m sprint time (20m), T-test time, and sit and reach (SR) distance. All TMG measures were analyzed using a three-way [condition × time x leg] analysis of variance (ANOVA). All performance variable data were analyzed with a repeated measures ANOVA. RESULTS: There was no difference between warm up protocols for T-test, CMJ-h, or CMJ-ft. 20m significantly improved following SSG (p=0.020) compared to DYN and PLY. SR was significantly greater following PLY (p=0.022). Three-way ANOVA did not reveal a significant interaction for any of the measured TMG variables. However, main effects of time were seen PRE to POST for BF-Tc (p=0.035), RF-Td (p<0.001) and BF-Td, (p=0.008) and a main effect of condition was seen for RF-Tc (p=0.038). CONCLUSION: Warm-up specific improvements were demonstrated in sprint speed and flexibility measures following SSG and PLY, respectively. While no differences were shown between the examined protocols, the present study revealed PRE to POST changes in certain TMG measures (RF-Td, BF-Td, and BF-Tc) following a warm up in male collegiate soccer athletes.